Data-Mining Approaches Reveal Hidden Families of Proteases in the Genome of Malaria Parasite - Wu, Yimin; Wang, Xiangyun; Liu, Xia; Wang, Yufeng (Genome Research, 2003)
The search for novel antimalarial drug targets is urgent due to the growing resistance of Plasmodium falciparum parasites to available drugs. Proteases are attractive antimalarial targets because of their indispensable roles in parasite infection and development, especially in the processes of host erythrocyte rupture/invasion and hemoglobin degradation. However, to date, only a small number of proteases have been identified and characterized in Plasmodiumspecies. Using an extensive sequence similarity search, we have identified 92 putative proteases in the P. falciparum genome. A set of putative proteases including calpain, metacaspase, and signal peptidase I have been implicated to be central mediators for essential parasitic activity and distantly related to the vertebrate host. Moreover, of the 92, at least 88 have been demonstrated to code for gene products at the transcriptional levels, based upon the microarray and RT-PCR results, and the publicly available microarray and proteomics data. The present study represents an initial effort to identify a set of expressed, active, and essential proteases as targets for inhibitor-based drug design.[Supplemental material is available online at www.genome.org.]